x-5x=7x-9x-x

Simple and best practice solution for x-5x=7x-9x-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-5x=7x-9x-x equation:


Simplifying
x + -5x = 7x + -9x + -1x

Combine like terms: x + -5x = -4x
-4x = 7x + -9x + -1x

Combine like terms: 7x + -9x = -2x
-4x = -2x + -1x

Combine like terms: -2x + -1x = -3x
-4x = -3x

Solving
-4x = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-4x + 3x = -3x + 3x

Combine like terms: -4x + 3x = -1x
-1x = -3x + 3x

Combine like terms: -3x + 3x = 0
-1x = 0

Divide each side by '-1'.
x = 0

Simplifying
x = 0

See similar equations:

| X+0.375=-1.75 | | -328=-56b+7 | | -5+4r=-5r+4r | | 19-13p=-5-17p | | 0.5+0.5j=0 | | ln(5X+1)=4.5 | | 3x+12=7x-22 | | x+3(x-3)=91 | | 2x=-16+4y | | 3x-66=9x | | 1+k=3k-1 | | -0.6+y=-0.33 | | -28=v-18 | | 20+18x-2=21x | | X-9.2=-4.55 | | 4=p-1 | | X-1.25=3.5 | | 0.5-0.5j=0 | | 2(h+3)+1=9 | | 0=-9(b-1) | | x^2+3-12=0 | | 12x^3-8x^2-35x+6=0 | | (2x+4)(x)=20 | | X+0.3=-0.4 | | -6.75=x+5.4 | | 4(2x+4)=10x+15-2x+17 | | 265=-5x | | 14=k+9 | | 5-6w=-13 | | 9x-2+55=13+14x | | -4x-36=-72 | | -16+m=-20 |

Equations solver categories